Ultrassonografia e CA-125 como preditores de malignidade em mulheres com tumores anexiais - Hartman, Caio Augusto, 1977- (2012)
Orientadores: Sophie Françoise Mauricette Derchain, Cássia Raquel Teatin Juliato